2015
DOI: 10.1590/01000683rbcs20140432
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Uncertainty of Nutrient Loss by Erosion in Sugarcane Harvesting Scenarios

Abstract: the assessment of spatial uncertainty in the prediction of nutrient losses by erosion associated with landscape models is an important tool for soil conservation planning. the purpose of this study was to evaluate the spatial and local uncertainty in predicting depletion rates of soil nutrients (p, K, ca, and Mg) by soil erosion from green and burnt sugarcane harvesting scenarios, using sequential gaussian simulation (SgS). a regular grid with equidistant intervals of 50 m (626 points) was established in the 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 20 publications
(21 reference statements)
0
1
0
Order By: Relevance
“…Research has shown that the main method of nutrient loss is water runoff (Oliveira et al 2015, Adviento-Borbe et al 2018. Thus, soil impoverishment is linked to sediment transport and soil slope (Mendonça et al 2015). Bramorski et al (2015) evaluated nitrogen losses resulting from water erosion and found that the loss of nutrients negatively affects the https://doi.org/10.1590/1678-4499.20230191…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that the main method of nutrient loss is water runoff (Oliveira et al 2015, Adviento-Borbe et al 2018. Thus, soil impoverishment is linked to sediment transport and soil slope (Mendonça et al 2015). Bramorski et al (2015) evaluated nitrogen losses resulting from water erosion and found that the loss of nutrients negatively affects the https://doi.org/10.1590/1678-4499.20230191…”
Section: Introductionmentioning
confidence: 99%